The effect of Pegagan ethanolic extract (Centella asiatica L) self-nanoemulsifying drug delivery system (SNEDDs) in the development of Zebrafish embryos (Danio rerio) - Hayati, Farida; Chabib, Lutfi; Fauzi, Silmi; Awaluddin, R; , Sumayya; Mohd Nasir, Mohd Hamzah; Faizah, Wan Syarifah (2019)
INTRODUCTION PegaganThe pegagan is a traditional medicinal plant with the three major bioactive properties, triterpenoid, steroids, and saponin. It has the properties of antioxidant, anti-stress, and wound healing. Pegagan extract is prepared was made in Self-Nano emulsifying Drug Delivery Systems (SNEDDS) to overcome the problem of pegagan extract which has a low water-solubility level on water.